Preparation and Characterization of Activated Carbon from Waste Ion-Exchange Resin for CO2 Adsorption - Mengqi Wei; Qingbo Yu; Qiang Guo; Zongliang Zuo; Qin Qin (The Minerals, Metals and Materials Society, 2018)
Activated carbons, derived from waste ion-exchange resin by CO2 physical activation, were applied to separate CO2 from flue gas against global warming. The BET specific surface areas of activated carbons at different activation temperatures and times were investigated. The CO2 adsorption capacity was tested under non-isothermal and isothermal conditions. The experimental results show that when keeping the activation temperature constant, the specific surface area increases firstly and then decreases with increasing activation time. For the given activation time, the specific surface area rises firstly and then declines with increasing activation temperature. The adsorption capacity decreases with increasing temperature. The maximum adsorption capacity is 51.46 mg/g under the condition of 298 K and pure CO2. Fractional order kinetic model is the best one to describe the kinetics of CO2 adsorption. The activated carbons show the potential to be an effective adsorbent for the removal of CO2 from flue gas.